Novel ion exchange chromatography method for nca arsenic separation. (April 2017) - Oláh, Z.; Kremmer, T.; Vogg, A.T.; Varga, Z.; Szűcs, Z.; Neumaier, B.; Dóczi, R.
Abstract: A high-performance liquid chromatography (HPLC) device equipped with an anion exchange column was used to isolate nca 77 As from reactor irradiated nat GeO2 targets. The oxidation states of the isotope 77 As during the process was verified by thin layer chromatography. The radionuclidic purity of the separated fractions was checked by gamma measurements and it was found to be 99.91% for the As fraction. The elaborated method was applied to separate the isotope 74 As from cyclotron irradiated nat GeO2 targets too. Highlights: A HPLC anion exchange method is developed for 77 As separation from nat GeO2 target. The radionuclidic purity was found to be 99.91% for the As fraction. The method was applied for the production of the PET isotope 74 As too.